Primary Sjögren's Syndrome Presenting as Recurrent Ischemic Strokes. (April 2022) - Kesav, Praveen; Hussain, Syed Irteza; Devnani, Preeti; Namas, Rajaie; Al-Sharif, Khalid; Thomas, Moncy; Altrabulsi, Basel; John, Seby
Primary Sjogren's Syndrome (PSS) is an autoimmune exocrinopathy, with protean manifestations affecting multiple organ systems. Neurological manifestations are documented in about 20% of PSS cohorts in literature, with peripheral manifestations being commoner. Central nervous system manifestations of PSS (CNS-SS) encompass ischemic strokes, demyelinating lesions, aseptic meningitis, encephalitis, cerebellar ataxia, cognitive impairment and movement disorders. Ischemic stroke as presenting manifestation of PSS is extremely rare. We hereby describe a 50-year-old male, who presented for evaluation of 2 episodes of discrete focal neurological deficits over a duration of 6 weeks, with neuro-imaging findings revealing evidence of acute-subacute bihemispheric infarcts. Further evaluation revealed evidence of strongly positive anti phospholipid antibodies (aPL), indirect immunofluorescence antinuclear antibody (IIF-ANA), anti Sjögren's syndrome-A (SS-A/Ro) and anti-Ribonuclear protein (RNP) antibodies, with histopathological evidence of periductal and periacinar lymphocytic infiltration as well as acinar atrophy and interstitial fibrosis of minor salivary glands on lip biopsy, consistent with a diagnosis of Sjögren's syndrome, constituting a diagnosis of Antiphospholipid syndrome (APS) associated with PSS.